Teknologi Kecerdasan Buatan dalam Sistem Identifikasi Benih: A Review - Hidayat, Sidiq Syamsul; Rahmawati, Dwi; Triyono, Liliek; Prahara, Tahan; Prabowo, M. Cahyo Ardi (Agropross : National Conference Proceedings of Agriculture, 2022)
Revolution made various advances in various fields, including agriculture. Agricultural technology is very influential in supporting the increase in agricultural production. Inspection of rice seeds is an important process in plant nurseries because it will have an impact on the amount of rice production. The majority of inspection processes are currently carried out conventionally, namely by expert inspectors who manually screen rice seed samples to identify species and quality of rice seeds. The conventional rice seed inspection process has several obstacles, namely the role of humans in carrying out inspections is still very large and it requires quite a lot of time in determining the results of rice seed inspections. The use of technology is expected to increase productivity in agricultural production, speed, and accuracy in the rice seed inspection process. Intelligence Technology. Artificial provides an alternative to the inspection process automatically, accurately and quickly. We present a design study of technology related to seed identification systems using Machine Learning and Machine Vision methods to classify the quality of rice seed varieties. This technology is designed to identify superior and non-superior seeds based on digital image data training. So that the inspection process is helped because the machine can help identify the characteristics of superior seeds and are not based on digital image data processing.